Nacre-mimetic alternating architecture of AgSnO2 contact: Highly-efficient synergistic enhancement of in-situ self-repairing erosion resistance and naturally evolving impact resistance - Changhu Xu; Kai Wen; Zhe Wang; Jun Wang; Hailin Lu; Zesen Mao; Tianci Mao; Chongqing Fan; Jun Li (Journal of Materiomics)
Synergistically enhancing the erosion and impact resistance of contacts poses a significant challenge for cutting-edge electrical equipment. Fortunately, mollusk shells in nature have evolved effective strategies to construct microstructures with superior erosion and impact resistance. Inspired by the structure of nacre, AgSnO2 contact material with hierarchical architectures has been designed and fabricated. The mechanistic link between microstructural evolution and dynamic erosion is studied through experiments combined with Computational Fluid Dynamics (CFD) and Finite Element Method (FEM) simulations. Results show that the reconstructed SnO2 skeleton endowed with a highly continuous and anisotropic ‘flowering'-like structure forms a continuous interpenetrating network with Ag, optimizing the conductive pathways on the molten pool surface. Additionally, the Ag-rich regions in the deeper layers on both sides of the molten pool offers a stable ‘nutrient-supply’ for the continuous ‘flowering’ reconstruction of the skeleton, exhibiting excellent in-situ self-repairing erosion resistance. Benefiting from this synergistic strategy, this skeleton is reconstructed based on its natural structure, which further disperses the stress and deformation concentration while inhibiting interfacial debonding, thereby reducing the formation of cracks and significantly enhancing the impact resistance. This work is expected to breakthrough erosion and impact resistance in extreme condition electrical contact materials through biomimetic microstructure design.